Mitigation of 3.5 GHz Electromagnetic Field-Induced BV2 Microglial Cytotoxicity by Polydeoxyribonucleotide - Shailashree Pachhapure; Amila Mufida; Qun Wei; Jong-Soon Choi; Byeong-Churl Jang (Current Issues in Molecular Biology)
Emerging evidence highlights the biological risks associated with electromagnetic fields (EMFs) generated by electronic devices. The toxic effects and mechanisms induced by exposure to EMFs on microglial cells and natural substances that inhibit them are limited to date. Here, we investigated whether exposure to 3.5 GHz EMF radiation, potentially generated by smartphones working in 5G communication or cooking using microwave ovens, affects the growth of BV2 mouse microglial cells and polydeoxyribonucleotide (PDRN), a DNA preparation derived from salmon sperm, inhibits it. Of note, exposure to 3.5 GHz EMF radiation for 2 h markedly inhibited the growth and triggered apoptosis in BV2 cells, characterized by the reduced number of surviving cells, increased genomic DNA fragmentation, increased reactive oxygen species (ROS) levels, and altered phosphorylation and expression levels of JNK-1/2, p38 MAPK, ERK-1/2, eIF-2α, and procaspase-9. Pharmacological inhibition studies revealed that JNK-1/2 and p38 MAPK activation and ROS generation were crucial for 3.5 GHz EMF-induced BV2 cytotoxicity. Of interest, PDRN effectively countered these effects by inhibiting the activation of JNK-1/2, p38 MAPK, and caspase-9, and the production of ROS, although it did not affect eIF-2 phosphorylation. In conclusion, this study is the first to report that PDRN protects against 3.5 GHz EMF-induced toxicities in BV2 microglial cells, and PDRN’s protective effects on 3.5 GHz EMF-induced BV2 cytotoxicity are mediated primarily by modulating ROS, JNK-1/2, p38 MAPK, and caspase-9.